The atlas of North American English phonetics, phonology and sound change : a multimedia reference tool - Labov, William 1927-2024; Ash, Sharon; Boberg, Charles 1984- (Mouton De Gruyter, 2006)
The Atlas of North American English provides the first overall view of the pronunciation and vowel systems of the dialects of the U.S. and Canada. The Atlas re-defines the regional dialects of American English on the basis of sound changes active in the 1990s and draws new boundaries reflecting those changes. It is based on a telephone survey of 762 local speakers, representing all the urbanized areas of North America. It has been developed by Bill Labov, one of the leading sociolinguists of the world, together with his colleagues Sharon Ash and Charles Boberg. The Atlas consists of a printed volume accompanied by an interactive CD-ROM. The print and multimedia content is also available online. Combined Edition: Book and Multimedia CD-ROM The book contains 23 chapters that re-define the geographic boundaries of North American dialects and trace the influence of gender, age, education, and city size on the progress of sound change; findings that show a dramatic and increasing divergence of English in North America; 139 four color maps that illustrate the regional distribution of phonological and phonetic variables across the North American continent; 120 four color vowel charts of individual speakers. The multimedia CD-ROM supplements the articles and maps by providing a data base with measurements of more than 100,000 vowels and mean values for 439 speakers